Therapeutic effect of transmembrane TAT-tCNTF via Erk and Akt activation using in vitro and in vivo models of Alzheimer’s disease - Bi, Guofang (Int J Clin Exp Pathol, 2018)
Suppressing Alzheimer’s disease (AD) progression via its pathological characteristics, namely senile plaques and neurofibrillary tangles, is an efficient treatment approach. Numerous studies have indicated that ciliary neurotrophic factor (CNTF) not only promotes neuronal growth and maintains cell survival but also significantly reduces amyloid beta (Aβ) aggregation and deposition. In this study, transactivator of transcription (TAT) was linked to truncated ciliary neurotrophic factor (tCNTF) and expressed as a fusion protein, TAT-tCNTF, to overcome the transmembrane inability of CNTF. Accordingly, TAT-tCNTF was shown to automatically transport across biomembranes and enter cells mainly by macropinocytosis. Furthermore, TAT-tCNTF increased cell viability in hippocampal neurons treated with Aβ. After intracerebroventricular Aβ injection, mice exhibited amyloid deposits, which were significantly reduced after intraperitoneal TAT-tCNTF injection. Indeed, TAT-tCNTF significantly reduced Aβ-induced tau hyperphosphorylation, and yet barely affected amyloid precursor protein. Accordingly, it was possible to elucidate its potential pharmacological mechanism, with the working effect of TAT-tCNTF shown to be performed by specifically binding to its receptor, CNTFRα, and then activating the Extracellular regulated protein kinases (Erk) and Protein kinase B/Akt pathways exclusive of the Signal transducers and activators of transcription 3 (Stat3) pathway.